Immobilization of heparin onto the novel cellulose:chitosan vascular grafts: A preliminary study - Azevedo, Eduardo Pereira; Kumar, Vijay (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Purpose: The aim of this study was to prepare a compliant cellulose:chitosan hollow tube (with 6 mm in internal diameter), to be used as a coronary bypass graft, and to investigate its ability to covalently immobilize heparin onto its surface. Method: Cellulose and chitosan solutions were mixed in equal proportions, spread in an appropriate mold and allowed to solidify for 24 hours, where a hollow tube was obtained. Heparin was covalently immobilized onto these hollow tubes, where the results were compared with that of a plain cellulose one. In addition, a correlation between the heparin concentration and the immobilization efficiency was investigated. Results: The presence of chitosan was essential for the heparin immobilization onto the cellulose:chitosan hollow tubes as no heparin was immobilized onto the plain cellulose ones. The immobilization density showed to be linearly dependent upon the concentration of the activated heparin, where a maximum concentration of 4 mg/mL was reached. Higher concentrations of activated heparin did not provide a greater immobilization density, which indicates that the amine groups of chitosan have been saturated. Conclusion: The cellulose:chitosan hollow tubes were successfully prepared, where the presence of chitosan was required for an efficient immobilization of heparin. The obtained heparin-immobilized cellulose:chitosan hollow tube, with its mechanically strong, reasonably compliant and antithrombogenic properties seems to be a good candidate to be used as a vascular bypass graft.